Dima spicata Schimmel, 1999 (Elateridae: Dimini), a morphologically remarkable species endemic to China - Qiu, Lu; Németh, Tamás; Prosvirov, Alexander S.; Kundrata, Robin (Zootaxa, 2020)
Dima spicata Schimmel, 1999 has a unique pronotal morphology within Dimini, with the posterior angles extremely elongate and surpassing humeral part of elytra. It was described based on a female specimen from Southwest China (Sichuan, Ya’an). Here, we report the discovery of additional specimens including males from several localitites in Liangshan, Sichuan. We redescribe the species in detail and discuss its intraspecific variability and distribution.